A SYSTEMATIC LITERATURE REVIEW: ETHNOMODELLING AS CULTURALLY SITUATED MATHEMATICAL MODELLING - Melkior Wewe; I Gde Wawan Sudatha; I Kadek Suartama; Made Hery Santosa (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
Ethnomodelling has emerged as a bridge between ethnomathematics and mathematical modelling, yet its conceptual boundaries and methodological applications remain fragmented. This review examines how culturally situated mathematical practices are transformed into mathematical models, learning tasks, digital resources, learning trajectories, and curriculum designs in mathematics education. Guided by PRISMA 2020 principles, this study employed a systematic review and conceptual synthesis. Relevant studies were identified through database searching and citation chasing using multilingual keywords in English, Indonesian, Portuguese, and Spanish. After duplicate removal, title and abstract screening, full-text assessment, and quality appraisal, 26 empirical, design-based, and conceptual studies were included. A hybrid SPIDER/PICo framework guided study selection, data extraction, and thematic-conceptual analysis. The synthesis revealed four major trajectories: theoretical ethnomodelling grounded in emic, etic, and dialogical translation; modelling of cultural artifacts such as architecture, calendars, Indigenous number systems, games, food practices, and symbolic patterns; classroom and digital design through worksheets, GeoGebra, and learning trajectories; and equity-oriented humanization of mathematics through local and Indigenous knowledge. Ethnomodelling should be understood as culturally situated mathematical modelling, not decorative cultural contextualization. Future studies need stronger designs, clearer outcomes, and ethical engagement with the communities from which cultural knowledge is derived.